Continuous Improvement in Teaching and Learning for Quality Insurance In Jordanian Universities - Hussein Elyan AL Haramsheh (University of Science and Technology, Yemen, 2015)
This study aimed to identify the level of Cotuniuse Improvement in Teaching and Learning for  Quality Insurance In Jordanian Universities and new technique to ensure the quality of higher education , as well as identify the obstacles that prevent the use innovation and new technique in the educational process, by testing the following hypothesis: 1 - higher educational institutions do not use the Cotuniuse Development and Improvement 2 - There are some obstacles that prevent the use of Cotuniuse Development and Improvement 3 - there is a correlation between the presence of obstacles and obstruct using Cotuniuse Development and Improvement, the study population consisted of the members faculty of  ( Zarqa University , Hashemite University, Al-Balqa University ),about ( 100 ) questionnaires were distributed, and ( 94) were restored to identify analysis valid, the recovery rate was 94 %. the questionnaire was build and develop to collect the necessary data, it consists of two parts and (40) statements, the most important results was : higher education institutions use Cotuniuse Development and Improvement was moderately, restriction of lecture plan and educational policies is one of the more constraints, a strong correlation between the existence of obstacles and the prevention of use Cotuniuse Development and Improvement, recommendations : encourage faculty members to deliver a flexible lecture plan, and use new methods in education, It also encourages students to participate, interact, and dialogue through lectures , It is very important to adapt a clear vision for using new style of innovation in the educational process ,It should focus on strengthening individual affiliation of the country, and focus on providing students with the skills of creativity and innovation. Key words: creative education, innovation, quality of higher education